2021
DOI: 10.1155/2021/4190098
|View full text |Cite
|
Sign up to set email alerts
|

Shenjinhuoxue Mixture Attenuates Inflammation, Pain, and Cartilage Degeneration by Inhibiting TLR‐4 and NF‐κB Activation in Rats with Osteoarthritis: A Synergistic Combination of Multitarget Active Phytochemicals

Abstract: Osteoarthritis (OA), a highly prevalent chronic joint disease, involves a complex network of inflammatory mediators that not only triggers pain and cartilage degeneration but also accelerates disease progression. Traditional Chinese medicinal shenjinhuoxue mixture (SHM) shows anti-inflammatory and analgesic effects against OA with remarkable clinical efficacy. This study explored the mechanism underlying anti-OA properties of SHM and evaluated its efficacy and safety via in vivo experiments. Through network ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 93 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…This is also confirmed by the intranuclear expression of NF-κB p65. In a similar study ( Ma et al, 2021 ), the inhibition of the TLR-4/NF-κB pathway effectively reduced cartilage degradation and inflammatory response in rats.…”
Section: Discussionmentioning
confidence: 84%
“…This is also confirmed by the intranuclear expression of NF-κB p65. In a similar study ( Ma et al, 2021 ), the inhibition of the TLR-4/NF-κB pathway effectively reduced cartilage degradation and inflammatory response in rats.…”
Section: Discussionmentioning
confidence: 84%
“…TLR signalling pathway is very important in the pathogenesis of OA. 46,47 Researchers concluded that Peli1 promotes TLR signalling and proinflammatory cytokine production. 24 However, how Peli1 regulates TLR signalling has not been studied in chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, relatively smaller doses of herbs are considered at “Jwa” and “Sa” to reduce adverse effects or boost synergistic effects. Thus, a suitable herbal combination can exhibit amplified efficacy compared to a single herb [ 30 , 116 , 117 , 118 , 119 , 120 ]. To establish these synergistic effects, an appropriate combination of EAHMs must be selected for drug development.…”
Section: Discussionmentioning
confidence: 99%